Consumer-centered sustainability : A study on Gen Z’s motivation to engage in transformable garment co-design - Zhen, Zeng; Marzie, Hatef Jalil (Arts and Science Press Pte. Ltd., 2025)
Employing a Transformable Garment Co-Design (TGCD) represents a sustainable design strategy that provides a solution for balancing resource conservation with consumer demands for enhanced lifestyle quality. However, the willingness to accept this innovative approach remains underexplored, and the key factors influencing their readiness have yet to be identified. Drawing on the theory of planned behaviour (TPB), this study aims to investigate the roles of appreciation for aesthetics and functionality (from a positive attitude) and perceived prior experience (from perceived behavioral control) as significant variables impacting the willingness of the young consumer, particularly Gen Z, to engage with TGCD. A quantitative research method was used, utilizing random sampling and collecting data through a survey of Gen Z university students in Zhejiang Province, China. A total of 375 respondents participated in the survey. Hotelling’s T-squared test in SPSS was employed to evaluate the significance of the proposed factors. The findings indicated that appreciation for aesthetics and functionality, as well as a positive attitude and perceived prior experience with TGCD, significantly influence Gen Z's willingness to adopt this design approach. This research extends the Theory of Planned Behavior (TPB). It contributes to the broader field of sustainable design, particularly within the context of Total Green Circular Design (TGCD) in China, by offering insights into the market potential of this innovative strategy in garment design.